Influence of combined therapy with prospidin and methotrexate on radiological progression, functional status and quality of life in pts with rheumatoid arthritis - O. V. Simonova; B. F. Nemtsov; N. N. Politova (Научно-практическая ревматология)
Objective. To evaluate influence of combination therapy with prospidin (P) and methotrexate (MTX) on X-ray progression, functional status (FS) and quality of life (QL) in patients with rheumatoid arthritis (RA) in comparison with MTX monotherapy. Material and methods. 143 RA pts (129 female and 14 male) were studied. Of them, there were. Mean age was 45.5±5.l years. Average duration of the disease was 4.5 years. 20 pts had II and 123 - 111 degree of RA activity. The second X-ray stage according to Steinbroker dominated. 72 pts of group I received P+MTX combination therapy. The therapy included intravenous drip-feed of P 200-300 mg per week in 200ml of 5% glucose and MTX 10 mg per week 1M. The maintaining therapy included P 100-200 mg per week IM and MTX 10 mg per week. 71 patients of group II received MTX monotherapy 10 mg per week. X-ray progression assessment was performed according to Sharp method. FS was evaluated with the HAQ questionnaire, Lee test. QL was evaluated with SF-36 scale. Pts were examined before and after I, 2, 3, 6 and 12 months of treatment. Results. There was no increase of X-ray progression of the disease in case of P+MTX therapy as compared with MTX monotherapy. Both methods resulted in improvement of FS parameters and physical health. Combination therapy significantly improved psychological health as well.